Capillary and Cavernous (Mixed) Type of Cervical Hemangioma with Uterine Adenomyosis in a 40-year-old Female (GAIMS Journal of Medical Sciences, 2025)
Hemangioma of the uterine cervix is an extremely rare benign vascular lesion and only a few sporadic cases have been reported. Cervical hemangioma is characterized by increase in the number of normal and abnormal veins. Histopathology examination is needed to diagnose hemangioma and to differentiate this disease with other pathological conditions. Hemangioma is a benign tumor which originates from endothelial cells of the blood vessels, which represent multipotent cellular elements, or from pericytes located on the outer side of the blood vessel wall. The majority of cervical hemangiomas have been reported in women of child bearing age.